2017
DOI: 10.5209/amal.54283
|View full text |Cite
|
Sign up to set email alerts
|

Gendering Globalized Flows in Bertrand Bonello’s Tiresia

Abstract: Abstract. Presented as the conciliatory voice of wisdom, Teiresias, the blind theban seer who had been both man and woman, exemplifies how transcending gender can lead to a questioning of normative, victimizing cultural mandates within the polis. This gender-bending acquires further applications in the 2003 film, Tiresia, about the myth-informed travails of a transsexual brazilian illegal immigrant prostitute in france. The film daringly deconstructs the dividing lines within contemporary globalized flows: imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Related to myth, the term neutral and gender fluidity correlates to the mythology of Tiresias from Oedipus. Dokou ( 2017) had found that in Bonello"s aestheticism, Tiresias has presented the gender-bending paradigm which blend also creativity between mythic universe with the paradoxes and archetype life in the medium of film. Thus, the recent gender phenomenon has been represented by myth in flowing images or symbols to explore that phenomenon itself.…”
Section: Introductionmentioning
confidence: 99%
“…Related to myth, the term neutral and gender fluidity correlates to the mythology of Tiresias from Oedipus. Dokou ( 2017) had found that in Bonello"s aestheticism, Tiresias has presented the gender-bending paradigm which blend also creativity between mythic universe with the paradoxes and archetype life in the medium of film. Thus, the recent gender phenomenon has been represented by myth in flowing images or symbols to explore that phenomenon itself.…”
Section: Introductionmentioning
confidence: 99%